Implementasi Perencanaan Pendidikan Nilai Tambah Bahasa Inggris di TK GAIS Montessori Sukabumi - Aliyah, Lia; Qomariyah, Siti; Putri, Ressy Resviati; Sumarni, Leni; Rahmawati, Ai Siti (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
English language education in early childhood must be carefully designed to function as developmental added value rather than an academic burden, particularly within institutions integrating Islamic values and the Montessori approach. This study aimed to analyze the implementation strategy of educational planning based on the added value of English at Golden Age Islamic School Montessori Sukabumi. A qualitative approach with a case study design was employed. The research subjects included the principal and homeroom teachers. Data were collected through observation, in-depth interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques.The findings reveal that English education planning at TK GAIS Montessori Sukabumi is systematically integrated into the Merdeka Curriculum for the foundational phase through bilingual learning that emphasizes thematic content and contextual vocabulary aligned with children’s developmental stages. Learning implementation is carried out in an enjoyable and child-centered manner through circle time, Montessori-based play activities, and a supportive bilingual environment that promotes natural English exposure. Teacher capacity and school management are strengthened through continuous professional development, regular clinical supervision, and stable parental financial support. Furthermore, learning and curriculum evaluations are conducted in a structured and reflective manner to maintain program quality and sustainability. This study concludes that educational planning based on the added value of English at TK GAIS Montessori Sukabumi effectively supports holistic, contextual, and developmentally appropriate English language acquisition in early childhood education.